Identification of a human melanoma antigen recognized by tumor-infiltrating lymphocytes associated with in vivo tumor rejection. - Kawakami, Y (1994)
The cultured T-cell line TIL1200, established from the tumor-infiltrating lymphocytes (TILs) of a patient with advanced metastatic melanoma, recognized an antigen on most HLA-A2+ melanomas and on all HLA-A2+ cultured neonatal melanocytes in an HLA-A2 restricted manner but not on other types of tissues or cell lines tested. A cDNA encoding an antigen recognized by TIL1200 was isolated by screening an HLA-A2+ breast cancer cell line transfected with an expression cDNA library prepared from an HLA-A2+ melanoma cell line. The nucleotide and amino acid sequences of this cDNA were almost identical to the genes encoding glycoprotein gp100 or Pmel17 previously registered in the GenBank. Expression of this gene was restricted to melanoma and melanocyte cell lines and retina but was not expressed on other fresh or cultured normal tissues or other types of tumor tested. The cell line transfected with this cDNA also expressed antigen recognized by the melanoma-specific antibody HMB45 that bound to gp100. A synthetic 10-amino acid peptide derived from gp100 was recognized by TIL1200 in the context of HLA-A2.1. Since the administration of TIL1200 plus interleukin 2 resulted in regression of metastatic cancer in the autologous patient, gp100 is a possible tumor rejection antigen and may be useful for the development of immunotherapies for patients with melanoma.